Una clientela militar entre la Corona de Aragón y Castilla a fines del siglo XIV: caballeros de casa y vasallos de Alfons d’Aragó, conde de Denia y marqués de Villena - Sáiz, Jorge (En la España Medieval, 2006)
The article focuses on the structure and functioning of a particular feudal affinity, that of Alfons of Aragó, count of Denia and marquis of Villena, from the 1360s to the 1390s. Aragó’s double condition, as Valencian lord and Castilian lord, made his clientage present organizational features from both the Crown of Aragon and the Crown of Castile, as can be seen through the rich household accounts preserved. Employing a broad concept of late feudal affinities, patterns of service and retribution of the low nobility gravitating around Alfons d’Aragó —both the household’s knights and squires, and the military vassals external to it— are examined. Finally, the performance of both groups as a military affinity is addressed through the study of feudal chivalry in the 1378-1379 war between Castile and Navarre.